2021
DOI: 10.1159/000515999
|View full text |Cite
|
Sign up to set email alerts
|

Annually Recurring Erythema Annulare Centrifugum: A New Case Series with Review of the Literature

Abstract: Annually recurring erythema annulare centrifugum (AR-EAC) is a rare variant, characterized by typical annular plaques recurring in the same period of the year. We describe 5 new cases and present a review of the literature. Patients were 3 females and 2 males with an age range of 25–55 years. Multiple annular plaques were located at the thighs in 4 patients and the neck in one patient. In 1 patient, a single lesion was present. Plaques were recurring in summer in 3 cases; in 1 case, in spring; and another pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…To make the topic even more intriguing, we recently reported a case of AR-EAC deep type with periadnexal involvement. [ 9 ] The immunophenotyping studies revealed a moderate number of CD123 + plasmacytoid dendritic cells, which are well documented in Jessner-Kanof and LET but not in EAC, with the caveat that only one case has been evaluated. [ 41 42 ] In conclusion, there is significant clinical and histological overlap between PMAE, Jessner-Kanof, LET, and EAC deep type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To make the topic even more intriguing, we recently reported a case of AR-EAC deep type with periadnexal involvement. [ 9 ] The immunophenotyping studies revealed a moderate number of CD123 + plasmacytoid dendritic cells, which are well documented in Jessner-Kanof and LET but not in EAC, with the caveat that only one case has been evaluated. [ 41 42 ] In conclusion, there is significant clinical and histological overlap between PMAE, Jessner-Kanof, LET, and EAC deep type.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 ] Only 14 cases have been described in the literature and have been recently reviewed. [ 9 ] Patient age ranged from 16 to 83 years, with a mean age of 47 years and a disease duration of 1–30 years. In most cases, AR-EAC has been observed in females, with an M:F = 1:2.4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annually recurring erythema annulare centrifugum is a very rarely reported variant of EAC which clinically and histopathologically simulates classic superficial EAC but recurs periodically in each year 1,2 . It has a female preponderance with a peak age of onset between 40 to 50 years 1,2 , this can range from 16 to 80 years. Even though this variant is idiopathic, a full diagnostic workup is mandatory to exclude any underlying disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Annually recurring erythema anulare centrifugum is a very rarely reported peculiar variant of EAC which has identical clinical and histopathological features to classic EAC 1 . Up to now very few similar cases are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%